2002
DOI: 10.1016/s0895-7061(01)02337-8
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term effects of ferulic acid on blood pressure in spontaneously hypertensive rats

Abstract: Ferulic acid (4-hydroxy-3-methoxycinnamic acid) is a phenolic compound contained in rice bran and other plants. The effect of ferulic acid on blood pressure (BP) was investigated in spontaneously hypertensive rats (SHR). After oral administration of ferulic acid (1 to 100 mg/kg) to SHR, systolic blood pressure (SBP) significantly decreased in a dose-dependent manner. When oral ferulic acid (50 mg/kg) was administered to SHR, BP was lowest at 1 h and returned to basal levels at 6 h. There was a significant corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
92
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(105 citation statements)
references
References 27 publications
6
92
0
1
Order By: Relevance
“…These effects may be a suppression of the ROS by FA treatments. These studies reported that FA treatment effectively decreased blood pressure levels (Suzuki et al, 2002). We used OLETF rats to determine whether FA has beneficial effects in type 2 diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects may be a suppression of the ROS by FA treatments. These studies reported that FA treatment effectively decreased blood pressure levels (Suzuki et al, 2002). We used OLETF rats to determine whether FA has beneficial effects in type 2 diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that FA is an antioxidant that neutralizes free radicals such as superoxide, nitric oxide and hydroxyl radicals that may cause oxidative damage to cell membranes and DNA (Kanski et al, 2002;Ha et al, 2008). FA provides meaningful synergistic protection against oxidative stress in the skin and should protect against photoaging and skin cancer (Lin et al, 2005), hypoglycemic and hypolipidemic effects (Sri Balasubashini et al, 2003;Ohnishi et al, 2004;Jung et al, 2007), hypotensive effects (Suzuki et al, 2002), and anti-inflammatory effects (Yagi and Ohishi, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…18 Oral administration of 50 mg kg À1 of ferulic acid also induced anti-hypertensive effect in both SHR and stroke-prone SHR (that is, SHRsp) models. 14,41 After digestion of ferulic acid in doses ranging from 0.5 to 50 mM, plasma levels of ferulic acid were elevated, with negatively correlated SBP changes ranging from À5 mm Hg to À15 mm Hg. 14 This evidence suggests that the CGA metabolites ferulic acid and, to a lesser extent, caffeic acid are responsible for the hypotensive effect seen in oral administration of CGA.…”
Section: Metabolites Of Chlorogenic Acid In the Bodymentioning
confidence: 99%
“…51 As discussed earlier, of the CGA metabolites, ferulic acid had greatest effect on BP reduction. 14,18 Interestingly, ferulic acid contained an ortho-methoxy-substituted-catechol structure (apocynin analogous) and had been implicated to work as a non-selective NAD(P)H oxidase antagonist by reacting with sulfhydryl groups. 52,53 In aortic rings pre-contracted with phenylephrine (an alpha-adrenergic neurotransmitter agonist), the administration of ferulic acid greatly increased NO bioavailability and enhanced acetylcholineinduced endothelial-dependent vasodilation, 35 but had no effect on sodium nitroprusside (a direct NO donor)-induced endotheliumindependent vasodilation, 19,35 signifying that vascular integrity (in particular intact endothelium) is essential for CGAs to lower BP.…”
Section: Molecular Targets Of Chlorogenic Acid In Blood-pressure Regumentioning
confidence: 99%
See 1 more Smart Citation